Repulsive axon guidance by Draxin is mediated by protein Kinase B (Akt), glycogen synthase kinase-3β (GSK-3β) and microtubule-associated protein 1B. - Rajeshwari Meli; Petronela Weisová; Friedrich Propst (PLoS ONE)
Draxin is an important axon guidance cue necessary for the formation of forebrain commissures including the corpus callosum, but the molecular details of draxin signaling are unknown. To unravel how draxin signals are propagated we used murine cortical neurons and genetic and pharmacological approaches. We found that draxin-induced growth cone collapse critically depends on draxin receptors (deleted in colorectal cancer, DCC), inhibition of protein kinase B/Akt, activation of GSK-3β (glycogen synthase kinase-3β) and the presence of microtubule-associated protein MAP1B. This study, for the first time elucidates molecular events in draxin repulsion, links draxin and DCC to MAP1B and identifies a novel MAP1B-depenent GSK-3β pathway essential for chemo-repulsive axon guidance cue signaling.